Study On The Development Of Attractions Puncak Langkisau Painan Kabupaten Pesisir Selatan - ASMARIZAL, ASMARIZAL; DRS. Bakaruddin, Ms, DRS. Bakaruddin, Ms; Drs. Edi Suarto, M.Pd, Drs. Edi Suarto, M.Pd (STKIP PGRI Sumbar, 2014)
ABSTRACTThis study aims to determine the development of attraction visits from Sapta charm and attraction development program for local attractions Puncak Langkisau Painan Kabupaten Pesisir Selatan.Qualitative research is research that aims to understand the phenomenon of what is experienced by the subject of the study such behavior, perception, motivation, action, holistic, and by means of a description in the form of words and language. The types of data needed in the study is primary data and secondary data. Primary data can be obtained from the interviews to obtain data and information that we need, while secondary data is data that can be obtained from the documents - documents that are associated with the problems to be studied.Informants in this study is the Head of Tourism Kepala Dinas Pariwisata Kabupaten Pesisir Selatan, Camat Kecamatan IV Jurai, communities living around the attraction, and visitors. The results of the study found that: 1) Sapta charm as security Attraction Puncak Langkisau Painan been maintained and managed properly, reflected in security, order, cleanliness, coolness, beauty, hospitality and memories. 2) development of program attractions Attractions Puncak Langkisau Painan Kabupaten Pesisir Selatan such as promotional programs and pemesaran is through internet media, print media and events, human resource development programs and institutions is to provide training and education, product development programs and tourist attraction that improved facilities, improved transport access and the development of attractions such as paragliding.